An Educational Program in Aesthetic Discourse for Postmodern Arts in Developing the Skills of Students of the Department of Art Education - Talib Jaafar, Ihsan; Allawi Meserbit, Hamza (International Journal of Psychosocial Rehabilitation, 2020)
The correct research included four chapters, the first of which was the research problem, in which the researcher felt the problem of his research and the necessity to study in this study. An educational program in the aesthetic discourse of postmodern arts to develop the skills of his request for the technical education section, and then presented the importance of research and research objectives and limits of research, which were limited to the trends of postmodern art of artistes' movements to the trends. The visual art and its elaboration in the material of the photographic construction of the request department of arts education at the College of Fine Arts, University of Baghdad, academic year 2017-2018, as well as the definition of search terms. The second chapter included the theoretical framework and consisted of three aspect of educational design: aesthetic discourse, the speech of postmodernism and movement visual art The theoretical framework, the third chapter, has adopted the preacher's methodical experimental research through the design of research tools consisting of the tests of pre-tribal and post-knowledge and skills and skills evaluation form as well as the presentation of variables research and procedures of application of experiment and the statistical methods and included chapter findings and the researcher's findings, and the researcher came out with a conclusion after the researcher put in a set of recommendations and suggestions.